Higher Means Harder for Female Descriptive Representation? Women with Family Responsibilities and Party Primaries for Local, Regional and National Chambers in Spain. Issue 4 (2nd October 2021) - Cordero, Guillermo; Pérez-Nievas, Santiago; Paradés, Marta; Coller, Xavier
ABSTRACT: Despite academic interest in the negative effects of primaries on gender descriptive representation, we have little evidence on how this impact varies across territorial levels, especially among women with family responsibilities. We focus on Spain as a multilevel polity (national, regional, local chambers) with mandatory quotas to show that very few females with family responsibilities are selected in primaries at upper territorial levels. While primaries frequently facilitate women becoming local councillors, this method seems to exclude those with family responsibilities at regional and national levels where, to fulfil gender quotas, female candidates are more commonly appointed by the party elite. This process has repercussions since representatives selected by the leadership tend to be more disciplined and homogeneous than those selected in primaries.